C-reactive protein binding to FcγRIIa on human monocytes and neutrophils is allele-specific - Stein, Mary-Pat (American Society for Clinical Investigation, 2000)
C-reactive protein (CRP) is involved in host defense, regulation of inflammation, and modulation of autoimmune disease. Although the presence of receptors for CRP on phagocytes has been inferred for years, their identity was determined only recently. FcγRIa, the high-affinity IgG receptor, binds CRP with low affinity, whereas FcγRIIa, the low-affinity IgG receptor, binds CRP with high affinity. Because the single nucleotide polymorphism in FcγRIIA — which encodes histidine or arginine at position 131 — strongly influences IgG2 binding, we determined this polymorphism’s effect on CRP binding. CRP bound with high avidity to monocytes and neutrophils from FcγRIIA R-131 homozygotes, and binding was inhibited by the R-specific mAb 41H16. CRP showed decreased binding to cells from FcγRIIA H-131 homozygotes (which bind IgG2 with high affinity). However, IFN-γ enhanced FcγRI expression by H-131 monocytes and increased CRP binding. FcγRIIa heterozygotes showed intermediate binding. CRP initiated increases in [Ca(2+)](i) in PMN from R-131, but not from H-131 homozygotes. These data provide direct genetic evidence for FcγRIIa as the functional, high-affinity CRP receptor on leukocytes while emphasizing the reciprocal relationship between IgG and CRP binding avidities. This counterbalance may affect the contribution of FcγRIIA alleles to host defense and autoimmunity.